2013
DOI: 10.1002/ajmg.a.35973
|View full text |Cite
|
Sign up to set email alerts
|

The value of the clinical geneticist caring for adults with congenital heart disease: Diagnostic yield and patients' perspective

Abstract: For adult patients with congenital heart disease (CHD), knowledge about the origin and inheritance of their CHD is important. Clinical geneticists may play a significant role in their care. We explored the diagnostic yield of clinical genetic consultation of adult CHD patients, patients' motivations for the consultation, implications for reproductive decisions, patients' evaluation of the impact of provided information, and satisfaction with counseling. Chart review was performed on all adult patients referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Recent surveys of adult CHD populations have demonstrated that a majority of patients lack proper understanding of their personal recurrence risks, but that provision and recall of genetic information can be significantly improved by incorporating genetic services into routine cardiovascular care 58,59 . Genetic counselors skilled in cardiovascular genetics have, consequently, become an invaluable clinical asset, helping to not only provide accurate recurrence risks, but also to obtain family and medical histories, facilitate appropriate genetic testing, interpret test results, make necessary subspecialty referrals, and provide attendant psychosocial support for patients and their families 60 .…”
Section: Genetic Services and Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent surveys of adult CHD populations have demonstrated that a majority of patients lack proper understanding of their personal recurrence risks, but that provision and recall of genetic information can be significantly improved by incorporating genetic services into routine cardiovascular care 58,59 . Genetic counselors skilled in cardiovascular genetics have, consequently, become an invaluable clinical asset, helping to not only provide accurate recurrence risks, but also to obtain family and medical histories, facilitate appropriate genetic testing, interpret test results, make necessary subspecialty referrals, and provide attendant psychosocial support for patients and their families 60 .…”
Section: Genetic Services and Counselingmentioning
confidence: 99%
“…Genetic counselors skilled in cardiovascular genetics have, consequently, become an invaluable clinical asset, helping to not only provide accurate recurrence risks, but also to obtain family and medical histories, facilitate appropriate genetic testing, interpret test results, make necessary subspecialty referrals, and provide attendant psychosocial support for patients and their families 60 . The importance of the cardiologist in promoting genetic services cannot be understated: most patients first hear about the possibility of genetic consultation from their cardiologist and a majority of these patients retroactively view the resulting genetics appointments positively 58,59 . These findings are particularly relevant in light of results from a non-scientific poll recently conducted at the 21st Annual International Adult Congenital Heart Disease (ACHD) Course which suggest that only 18% of ACHD practitioners regularly refer their patients for genetic evaluation and that only 25% regularly work alongside genetic counselors and clinical geneticists 60 .…”
Section: Genetic Services and Counselingmentioning
confidence: 99%
“…Genetic counselling in CHD has traditionally relied upon empiric recurrence risk values, 87,88 but rare CNVs can have a significant impact in specific cases. As in other domains, classic microdeletion syndromes like 22q11.2DS are the archetypal example of clinical applicability.…”
Section: Recurrence Risk Estimation and Genetic Counsellingmentioning
confidence: 99%
“…11,12 The benefits of evaluation by a geneticist and incorporation of genetic counseling have been demonstrated for many cardiovascular genetic conditions. [13][14][15] The complexity of current cardiovascular genetic evaluation and testing has led to guidelines recommending evaluation in centers with specialized expertise whenever possible to facilitate access to multidisciplinary teams that include cardiovascular clinicians, geneticists, and genetic counselors. 16,17 The expertise in the practice of any medical specialty is acquired not only through certified training but equally importantly through practical experience and patient interactions.…”
Section: Mital Et Al Enhancing Literacy In Cardiovascular Genetics 451mentioning
confidence: 99%
“…Before referral, a practitioner should discuss the reason for referral and the goals (eg, diagnosis, management, genetic testing, risk assessment, or prenatal counseling) with the patient. 13,36 Predictive testing, genetic testing in children, and prenatal testing are types of genetic testing that require additional domain-specific knowledge. 37,38 Who Should Be Tested Testing should be offered to an affected family member first.…”
Section: When Do I Refer For Genetic Testing?mentioning
confidence: 99%